POLITICAL COMMUNICATIONS AND TECHNOLOGIES IN CYBERSPACE: DIPLOMATIC VECTOR (MASS-INFORMATION SEGMENT) - Verkhovtseva, Iryna; TretiakOleksiі; Stavchenko, Serhiy; Alekseenko, Ihor (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
It was found that one of the leading dimensions of political-communication and political-technological activity in cyberspace is modern cyberdiplomacy, which includes digital communication both between diplomatic missions of different countries and between non-state foreign policy and global actors. It was found that the political communicativeness of modern diplomatic missions goes beyond the functions of state representation. It is established that the political and technological function of cyber diplomacy is the aggregation of resources in ensuring national interests, values and needs in the information environment. Cyberspace is characterized as a strategic center of gravity for modern states in contrast to traditional ideas about it as a specific technical sphere. It is found that the institutional and actor structure of political relations based on the Internet is characterized by its decentralized architecture and a significant role of private structures and civil society. It has been proven that non-state actors, including transnational criminal groups, «hacktivists» and cyber units of technology giants, demonstrate targeted political and technological influence in the international arena, comparable to the influence and capacity of small countries. It has been found that effective public cyber advocacy in this context involves political and technological (political marketing) setting clear expectations, stimulating cooperation and, when necessary, publicly holding platforms accountable for their failure to protect users or reduce the impact of harmful content. It is established that the ability of diplomatic missions of Ukraine to carry out «offensive"»(proactive) public communication activity is a crucial political and technological resource of cyber diplomacy. Its main content is the promotion of narratives about Ukraine’s successful struggle for its independence and the protection of the interests of the Euro-Atlantic community in the fight against the aggressor country. The mass-information segment of cyberspace is characterized, which determines the possibilities of political actualization of profile diplomatic functions on the basis of public-communication actions and campaigns. It is found that the proactive nature of political-technological (including public-communication actions) in the context of dialogue with the public, political actors and economic players of host countries is of great importance.